2015
DOI: 10.1523/jneurosci.4521-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of the Proteasome in the Early and Late Phases of BDNF-Induced Facilitation of LTP

Abstract: The neurotrophin brain-derived neurotrophic factor (BDNF) mediates activity-dependent long-term changes of synaptic strength in the CNS. The effects of BDNF are partly mediated by stimulation of local translation, with consequent alterations in the synaptic proteome. The ubiquitin-proteasome system (UPS) also plays an important role in protein homeostasis at the synapse by regulating synaptic activity. However, whether BDNF acts on the UPS to mediate the effects on long-term synaptic potentiation (LTP) has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…In contrast, no significant loss of Lin28a was observed over 3 hr in the presence of BDNF (Figure 1E). BDNF and excitatory neuronal activity are generally reported to increase ubiquitin-proteasome-mediated turnover of cellular proteins (Bingol and Schuman, 2006; Ehlers, 2003; Jia et al, 2008; Lin et al, 2011; but see Santos et al, 2015). However, taken together, these results indicate that rapid induction of Lin28a protein levels by BDNF occurs by enhanced Lin28a protein stability.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, no significant loss of Lin28a was observed over 3 hr in the presence of BDNF (Figure 1E). BDNF and excitatory neuronal activity are generally reported to increase ubiquitin-proteasome-mediated turnover of cellular proteins (Bingol and Schuman, 2006; Ehlers, 2003; Jia et al, 2008; Lin et al, 2011; but see Santos et al, 2015). However, taken together, these results indicate that rapid induction of Lin28a protein levels by BDNF occurs by enhanced Lin28a protein stability.…”
Section: Resultsmentioning
confidence: 99%
“…Proteasome activity is essential for the developmental effects of BDNF (Leal et al, 2014;Santos et al, 2015), a protein downregulated in schizophrenia (Jindal et al, 2010;Green et al, 2011;Zhang et al, 2012). Both activation and localization of proteasomes to synapses is essential for regulating synaptic strength and dendritic pruning, and phosphorylation of Rpt6 is necessary for activity-dependent localization of the proteasome to the synapse (Djakovic et al, 2012;Ertürk et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…, ), although recent studies also suggested a role for alterations in protein degradation by the proteasome (Santos et al . ).…”
Section: Plasticity Of Gabaergic Synapsesmentioning
confidence: 97%